2018
DOI: 10.1186/s13014-018-1114-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of a commercial knowledge-based VMAT planning for prostate cancer

Abstract: BackgroundThis study clarified the mechanical performance of volumetric modulated arc therapy (VMAT) plans for prostate cancer generated with a commercial knowledge-based treatment planning (KBP) and whether KBP system could be applied clinically without any major problems with mechanical performance.MethodsThirty consecutive prostate cancer patients who underwent VMAT using extant clinical plans were evaluated. The mechanical performance and dosimetric accuracy of the single optimized KBPs, which were trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…Additionally, the commercial diode array used in this work has been shown to provide accurate VMAT QA measurements despite this angular dependence . It is also important to note the results seen here with this specific combination of technologies (OVH‐guided KBP method, RayStation TPS, Elekta treatment machine, and MapCHECK2 diode array) may not hold for different KBP methods and planning, delivery, and measurement technologies as evidenced by the results from Tamura et al Regardless, the results of this study indicate that caution is needed regarding the effects of plan complexity and quality assurance outcomes when implementing any KBP system as they become more clinically prevalent. However, these results supplement the available literature showing KBP’s potential in providing immediate and substantial clinical impact.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Additionally, the commercial diode array used in this work has been shown to provide accurate VMAT QA measurements despite this angular dependence . It is also important to note the results seen here with this specific combination of technologies (OVH‐guided KBP method, RayStation TPS, Elekta treatment machine, and MapCHECK2 diode array) may not hold for different KBP methods and planning, delivery, and measurement technologies as evidenced by the results from Tamura et al Regardless, the results of this study indicate that caution is needed regarding the effects of plan complexity and quality assurance outcomes when implementing any KBP system as they become more clinically prevalent. However, these results supplement the available literature showing KBP’s potential in providing immediate and substantial clinical impact.…”
Section: Discussionmentioning
confidence: 67%
“…Likewise, Tamura et al . found no significant changes in patient‐specific quality assurance outcomes when using this commercial KBP system . Conversely, Kubo et al reported significantly increased MU values and higher plan complexity when using the same commercial KBP system as the studies noted previously .…”
Section: Introductionmentioning
confidence: 55%
“…[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 ] Our previous study showed that KBP with one-time auto-optimization could create an acceptable VMAT plan for prostate cancer that could be used in clinical practice with no major problems concerning dosimetric accuracy or mechanical performance. [ 10 16 ] Ueda et al suggested that sharing the KBP model could enable other institutions to reproduce the dose distributions, although whether the registered DVH curves match the plan design of the institution required verification. [ 17 ] However, the volumes over which high doses were delivered to organs at risks (OARs) in the KBP were inferior to those of clinical plans (CPs)[ 10 16 ] because the doses applied to any overlapping regions of the target and OARs were not considered in the KBP system.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 16 ] Ueda et al suggested that sharing the KBP model could enable other institutions to reproduce the dose distributions, although whether the registered DVH curves match the plan design of the institution required verification. [ 17 ] However, the volumes over which high doses were delivered to organs at risks (OARs) in the KBP were inferior to those of clinical plans (CPs)[ 10 16 ] because the doses applied to any overlapping regions of the target and OARs were not considered in the KBP system. [ 18 ] Some reports described the effects of outliers in the KBP model on the plan quality, or investigated whether a “cleaned-up” KBP model created by removing the outlier plans or structures which have potential of the negative effect on the model could improve the plan's quality.…”
Section: Introductionmentioning
confidence: 99%
“…RapidPlan predicts achievable dose-volume histograms (DVHs) and automatically generates optimization objectives to realize the prediction. Although the benefits of RapidPlan are still being investigated, there have been many reports of improvements in sparing organs at risk (OARs) using KBP (13)(14)(15)(16)(17)(18). The mechanical performance and dosimetric accuracy of KBP have also been verified, showing that KBP could be safely used in clinical practice (17)(18)(19).…”
mentioning
confidence: 99%